LEARNING AND TEACHER COLLABORATION IS AN IMPORTANT EDUCATIONAL PART OF INDEPENDENT WORK METHODOLOGY - Sayyora Turakhodjaevna Shermetova (Western European Studies, 2024)
In the article, a teaching model based on the scientific psychological-pedagogical concept of mastering the system of intellectual and practical skills in students, organizing education focused on the personality of the student is presented.
Keywords: educational and research work; subjective experience; creative activity